THE EFFECTIVENESS OF INTERACTIVE MULTIMEDIA TO INCREASE LEARNING OUTCOMES OF DEAF STUDENTS IN ELEMENTARY SCHOOL LEVEL: A LITERATURE STUDY - Putri Kartika Ningsih; Mohammad Efendi; Ediyanto Ediyanto; Asep Sunandar (Jurnal Pendidikan Humaniora, 2021)
Abstract: One of the consequences of obstacles to the hearing ability of deaf children is the difficulty of receiving and understanding verbal or audio learning materials. So the teacher needs to modify the way of delivering material to children by developing visual learning media, namely interactive multimedia. This research was conducted to determine the effectiveness of the development of interactive multimedia that can positively influence the learning outcomes of deaf students at the elementary school level. The research was conducted through a literacy study through Google Scholar with the keyword "the influence of interactive multimedia development for deaf students at the elementary school level," with a range of articles selected from 2015-2021. Based on the literacy study conducted, it was found that various applications were used to develop learning media in the form of interactive multimedia applications for deaf students. However, several interactive multimedias had not been applied to deaf students so that the effect of interactive multimedia on the learning outcomes of deaf students was unknown.Keywords: interactive multimedia, deaf, elementary school Abstrak: Salah satu akibat terhambatnya kemampuan mendengar anak tunarungu adalah sulitnya menerima dan memahami materi pembelajaran verbal atau audio. Sehingga guru perlu memodifikasi cara penyampaian materi kepada anak dengan mengembangkan media pembelajaran visual yaitu multimedia interaktif. Penelitian ini dilakukan untuk mengetahui keefektifan pengembangan multimedia interaktif yang dapat berpengaruh positif terhadap hasil belajar siswa tunarungu tingkat sekolah dasar. Penelitian dilakukan melalui studi literasi melalui Google Scholar dengan kata kunci “Pengaruh Pengembangan Multimedia Interaktif Bagi Siswa Tuna Rungu Tingkat Sekolah Dasar”, dengan rentang artikel yang dipilih dari tahun 2015-2021. Berdasarkan studi literasi yang dilakukan, ditemukan berbagai aplikasi yang digunakan untuk mengembangkan media pembelajaran berupa aplikasi multimedia interaktif untuk siswa tunarungu. Namun beberapa multimedia interaktif belum diterapkan pada siswa tunarungu sehingga belum diketahui pengaruh multimedia interaktif terhadap hasil belajar siswa tunarungu.Kata kunci: multimedia interaktif, tunarungu, sekolah dasar